Towing tank testing of passively adaptive composite tidal turbine blades and comparison to design tool. (February 2018) - Murray, Robynne E.; Ordonez-Sanchez, Stephanie; Porter, Kate E.; Doman, Darrel A.; Pegg, Michael J.; Johnstone, Cameron M.
Abstract: Passively adaptive bend-twist (BT) tidal turbine blades made of non-homogeneous composite materials have the potential to reduce the structural loads on turbines so that smaller more cost effective components can be used. Using BT blades can also moderate the demands on the turbine generator above design conditions. This paper presents experimental towing tank test results for an 828 mm diameter turbine with composite BT blades compared to a turbine with geometrically equivalent rigid aluminum blades. The BT blades were constructed of a graphite-epoxy unidirectional composite material with ply angles of 26.8° to induce BT coupling, and an epoxy foam core. For steady flow conditions the BT blades were found to have up to 11% lower thrust loads compared to rigid blades, with the load reductions varying as a function of flow speed and rotational speed. A coupled finite element model-blade element momentum theory design tool was developed to iterate between the structural (deformation and stresses) and hydrodynamic (power and thrust loads) responses of these adaptive composite blades. When compared to the experimental test results, the design tool predictions were within at least 8% of the experimental results for tip-speed ratios greater than 2.5. Highlights: A tidal turbine with composite bend-twist blades tested in steady conditions had 11% lower thrust loads compared to a turbine with rigid blades. The composite bend-twist blades induced slightly higher vibratory loads on the stanchion in steady flow conditions. A design tool predicted the thrust and torque measured experimentally to within 8% for tip-speed ratios above 2.5.